Pretreatments and temperature effects on the drying kinetics of peas - Doymaz, I.; Kucuk, I. (BULGARIAN ACAD SCIENCE, 2017)
In this study, peas were dried in convection dryer at a temperature range of 55-75 degrees C with a constant air velocity of 2 m/s. The peas were pre-treated with ethyl oleate and blanched with hot water at 85 degrees C before drying. Drying process continued until sample moisture fell down to 0.11 kg water/kg dry matter. The blanched samples dried faster than the other pre-treatment and control conditions. Besides, drying rate increased with increasing temperature. The experimental results illustrated the absence of constant-rate drying period and drying took place in the falling-rate period. Four well-known mathematical models were used to predict drying kinetics by nonlinear analysis of regression. Midilli and Kucuk model best fitted the experimental data for the whole range of temperatures. The moisture diffusivity coefficient at each temperature was determined by Fick's second law of diffusion, in which their value varied from 7.66x10(-11) m(2)/s to 2.44x10(-10) over the mentioned temperature range. The dependence of effective diffusivity coefficient on temperature was expressed by an Arrhenius type equation. The calculated values of the activation energy of moisture diffusion were 36.75, 38.11 and 43.25 kJ/mol for pre-treated with ethyl oleate, blanched samples and control samples, respectively.
Keywords: Activation energy; Drying; Effective diffusivity; Pea; Pre-treatments; GREEN PEAS; PISUM-SATIVUM; ETHYL OLEATE; MODEL; BEHAVIOR; Chemistry